Should we meet in person or on Facetime? An examination of expectancy violations and predicted outcome value forecasts during online dating modality switches - Sumner, Erin M.; Ramirez, Jr, Artemio; Herrera, Audrey (Human Communication & Technology, 2024)
The present study drew from expectancy violations theory, predicted outcome value (POV) theory, and the modality switching perspective to examine online daters who subsequently met for FtF-like communication. Hierarchical regression analyses tested whether online daters’ post-modality switch (MS) expectedness ratings, evaluations, and POV forecasts were related to their: (a) pre-MS length of online association; (b) number of pre-MS partner photos seen; (c) use of pre-MS phone calls; and (d) decision to hold the first FtF-like meeting in person or through video chat. Behavioral and physical appearance expectedness ratings were positively related to the number of pre-MS partner photos seen, and curvilinearly (inverted-u shape) related to daters’ pre-MS length of association. Physical appearance evaluations were positively associated with the number of pre-MS photos seen, while behavioral and physical appearance evaluations displayed positive associations with pre-MS phone calls. Finally, post-MS POV forecasts were positively associated with the number of pre-MS partner photos seen, holding the MS through video chat, post-MS assessments of a partner’s behavioral expectedness, and post-MS evaluations of a partner’s behavioral and physical appearance. An interaction also emerged for behavioral expectedness and evaluation on POV, which implied that negative expectancy violations were more useful than positive violations in predicting a relationship’s potential viability.